Optimization of Cultural Parameters for Improved Lipase Production by Enterobacter ludwigii from Fish Industry Waste - Husmin Risha. T; Dr. A.L. Hema Latha (The Bioscan, 2026)
Lipases are versatile enzymes with applications in detergents, biodiesel production, and the food industry. In this study, a lipase-producing bacterium was isolated from fish processing industry waste soil using Phenol Red Olive Oil Agar